Exploring the path to a low-carbon sustainable and equitable transition in China's dairy industry - Ma, Jinhong; Chen, Zhigang; Zhu Yonglei; Li Ting; Li, Yu; Wang, Binbin; Yang, Lirong; Zhu, Lei (Nature Conservancy, 2023)
As one of the representative industries of the agrifood system (agriculture and food system), the dairy industry integrates primary, secondary, and tertiary industries, involves animal husbandry, production and processing, end-consumption and recycling. Agri-food systems account for about 25-30%1of global GHG emissions. If the targets of Paris Agreement are to be achieved, it is a must to promote the systematic, pragmatic and resilient transformation for agri-food sector2. Since the signing of the Paris Agreement, the international community keeps calling for efforts to limit global temperature rise to 2 or 1.5 degrees Celsius by the end of the century. It has been reaffirmed during COP27 about the 1.5°C target, and also setting up the "Just Transition Pavilion" and "Food Pavilion" for the first time during COP. It can be found out that the increasing concerns about the equity and fairness to the vulnerably population in the process of low-carbon transition of agri-food systems. In addition, COP27 specifically called for the reduction of non-carbon dioxide greenhouse gas emissions, including methane, by 2030. Agriculture is the second largest source of methane emissions, after the energy sector. Livestock farming accounts for about 60% of these emissions, making it an indispensable pattern in the fight against climate change3. Alongside the China’s pathway to achieve carbon neutrality by 2060, in addition, to systematically advancing the development and reduction of energy, power, and industrial processes, the role of the agrifood system in achieving carbon neutrality is very critical. Systematic and in-depth research on it are necessary.